AN ANALYSIS OF ENGLISH EDUCATION DEPARTMENT STUDENTS' ABILITY IN TOEFL READING COMPREHENSION - Solpia Nuraini; Winda Trisnawati; Ridho Kurniawan (Journal Of Language Education and Development (JLed), 2022)
The TOEFL test is globally acknowledged as the foremost assessment tool for evaluating English proficiency levels (Warfield, 2013:133). This study explores the English department students' readiness for the TOEFL examination, with a specific focus on 4th-semester students enrolled in the TOEFL preparation class at STKIP MB. An observed issue pertains to reading comprehension difficulties encountered by students in this class. This difficulty primarily stems from the complexity and length of the texts, making it challenging to grasp the core ideas. Furthermore, students have been exposed to Academic Reading and Extensive Reading prior to the advanced Reading (TOEFL reading) section. This context demands specific skills such as extracting key ideas from passages, addressing direct and indirect questions, and enhancing vocabulary (Phillips, 2001). This research identifies a link between reading comprehension and reading techniques. Patel and Jain (2008:80) distinguish intensive, extensive, Aloud, and Silent reading techniques, with students struggling to maintain focus and comprehend texts effectively. Inefficient strategies often lead to time-consuming responses to reading comprehension questions. Another significant hurdle is that students tend to read passages word by word, hindering their ability to retain information. Harmar (2018:25) aptly notes, "Reading is an exercise dominated by the eyes and the brain," emphasizing that reading serves as a medium to obtain information and understand the meaning of text. However, the reality reveals a deficit in understanding words or sentences in English among some students, indicative of inadequate reading comprehension and limited vocabulary. This research also highlights the challenges faced by college students preparing for TOEFL, wherein tests exhibit varied formats, making them significantly different from typical assessments. The abundance of seemingly correct answer choices often perplexes students, leading to confusion and inconsistency in selecting the right answers. Furthermore, the students frequently grapple with tense usage and vocabulary limitations in the English language. Notably, reading comprehension consistently emerges as the lowest-scoring section in the TOEFL test. In conclusion, this study aims to address the reading comprehension difficulties encountered by STKIP MB 4th Semester Students in the TOEFL preparation class. By examining the correlation between reading techniques, comprehension strategies, and vocabulary enhancement, the research strives to provide effective solutions to improve TOEFL reading scores and overall English proficiency among students.